Nutritional, chemical and bioactive profiles of different parts of a Portuguese common fig (Ficus carica L.) variety - Palmeira, Luís (2018)
This study aims to give an unprecedented contribution on the chemical composition and bioactivities of the most produced and appreciated Portuguese fig variety (“Pingo de Mel”) with the view of expanding the knowledge on its potentialities. An advanced characterization of its peel and pulp parts was carried out. Four free sugars (glucose, fructose, trehalose and sucrose), 5 organic acids (oxalic, quinic, malic, citric, and succinic acids), tocopherols in all their 4 forms, besides 23 fatty acids were detected in the samples. Fifteen different phenolic components were found in the peel hydroethanolic extract; whereas 12 were detected in the pulp hydroethanolic extract. Quercetin-3-O-rutinoside (rutin) was the major constituent of the peel, accounting for 33.8% of its phenolic content, followed by 5-O-caffeoylquinic acid and vanillic acid malonyl di-deoxyhexoside. Caffeic acid derivatives, such as caffeic acid hexosides, were the major components of pulp, followed by vanillic acid derivatives and O-caffeoylquinic acid. Both extracts displayed promising antioxidant capacities in all methods used, namely the 2,2-diphenyl-1-picrylhydrazyl radical-scavenging, the reducing power, the inhibition of β-carotene bleaching assays, the thiobarbituric acid reactive substances assay and the oxidative haemolysis inhibition assay; however, the peel presented significantly lower IC50 values than pulp. The extracts showed practically identical antibacterial capacities, being effective against methicillin-sensitive Staphylococcus aureus (MICs=2.5 mg/mL), besides methicillin-resistant S. aureus, Escherichia coli and Morganella morganii (MICs=5 mg/mL). The obtained results evidence that the fig peel is superior to the corresponding pulp as it relates to nutritional and phenolic profiles as well as bioactivities, endorsing the urgency in valorising and exploiting this usually discarded industrial by-product.